OFR-24-73 Dust Suppression In Coal Mines (The National Institute for Occupational Safety and Health (NIOSH), 1972)
Contract No. H0110929 was awarded by the U.S. Bureau of Mines in February, 1971, to DeTer Company, Incorporated, of Mountain Lakes, N. J. The contract provided for the modification of the contractor's Model 5000 Pressure Foam Generator to fit it for the suppression of coal dust in mines, a detailed testing program in a working coal mine, and for additional modifications and testing for the suppression of fires in coal mines. The contractual program was completed in April, 1972. The results of the dust suppression tests showed conclusively that the modified DeTer equipment effectively reduced the level of respirable dust in a working coal mine well below the present and future acceptable levels set by the Mine Health and Safety Act of 1969. The fire tests, carried out in a simulated mine entryway erected on the surface, demonstrated the ability of the DeTer equipment in suppressing fires of varying degrees of severity within an acceptably short time.